Diabetes and Healing Outcomes in Lower Extremity Fractures: A Systematic Review. Issue 2 (February 2018) - Gortler, Hilary; Rusyn, Jessyca; Godbout, Charles; Chahal, Jas; Schemitsch, Emil H.; Nauth, Aaron
Abstract: Objective: The purpose of this study was to review the rates of adverse healing outcomes following surgical fixation of lower extremity fractures in diabetic patients and matched controls. Materials and Methods: Searches of PubMed, MEDLINE, CINAHL and Embase were performed for studies published between the date of database inception and July 6, 2015. Patient characteristics and the incidence of adverse healing outcomes (nonunion, malunion, delayed union, infection and reoperation) were extracted from each study. The occurrence of each fracture healing complication was pooled and analyzed for comparisons between diabetic and non-diabetic patients. An odds ratio with a 95% confidence interval for each healing outcome was calculated between the diabetic and non-diabetic groups. Results: Diabetes was found to significantly increase rates of malunion, infection and reoperation in patients with surgically treated lower extremity fractures. In addition, when only peripheral lower extremity fractures (i.e. below the knee) were examined, diabetes significantly increased the rates of nonunion. Conclusion: Diabetes substantially alters bone metabolism and soft tissue healing, posing a risk of adverse fracture healing and other complications. This systematic review provides evidence that the presence of diabetes significantly increases the risks of infection, malunion, nonunion and re-operation across a wide variety of surgically treated lower extremity fractures. This study provides prognostic information for clinicians and may aid in guiding treatment for this population.